Pengembangan Model Pembelajaran Berdiferensiasi Membaca Teks Eksposisi Berbasis Activity-Based Learning: Development of an Activity-Based Learning Model for Differentiated Reading Instruction of Expository Texts - Maimunah Maimunah; Miftahulkhairah Anwar; Gusti Yarmi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Instruction in reading expository texts at the junior high school level (SMP/MTs) continues to face various challenges, particularly students' low reading comprehension in interpretative and critical aspects. Furthermore, conventional teaching methods—often applied uniformly to all students—fail to accommodate differences in learning readiness, interests, and learning styles. This situation necessitates the development of an instructional model capable of addressing the diverse learning needs of students in heterogeneous classrooms. This study aimed to develop a differentiated reading instruction model for exposition texts for Grade VIII students at MTs Attaqwa Pusat Putri. The study employed the Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The developed products included a teaching module, student learning materials, a teacher's handbook, and "EXPO CARD" learning media; these were designed based on principles of content, process, and product differentiation, integrated with an Activity-Based Learning strategy. Data were collected through diagnostic assessments, interest and learning style questionnaires, expert validation (covering subject matter, language, and media), and product trials involving teachers and students. Validation results showed a 100% feasibility rate for subject matter and language (highly feasible), 90% for media (highly feasible with revisions), 91% for teacher trials (highly feasible), and 80.95% for student trials (feasible). Students' average scores improved from 59.64 (pre-test) to 78.93 (post-test). The developed differentiated instruction model for reading exposition texts is theoretically valid, practical to implement, and effective in enhancing students' reading skills, self-confidence, and learning motivation, while also assisting teachers in managing heterogeneous classrooms.